CRISPR/Cas9 uses : a review - Mimoune, Nora (Array, 2021)
Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR- associated system (Cas) is a system that provides immunity to most prokaryoticorganisms against viral attacks and other foreign bodies. CRISPR systems consist of a scissor-like protein called Cas9 and a genetic GPS guide "The guide RNA". However, researchers have reoriented and repurposed the primordial immune system to precisely manipulate genomes in most organisms by introducing DNA double-strand breaks at specific genome locations to introduce specific DNA modifications. More applications of CRISPR have arisen since its discovery, from disabling parasites to correcting mutations and improving crop yields. This review was conceived as a guide to CRISPR technology, from its discovery to the latest breakthroughs. It is hoped that this study will provide a general-based view for this life changing technology, inspiring scientists to go further with CRISPR in the sake of a better life.